Three-Dimensional Graphene-Supported Cobalt Phthalocyanine as Advanced Electrocatalysts for Oxygen Reduction Reaction. Issue 2 (1st January 2018) - Sun, Chongyun; Li, Zhongfang; Zhong, Xizhan; Wang, Suwen; Yin, Xiaoyan; Wang, Likai
Abstract : Cobalt phthalocyanine (CoPc) is supported on homemade three-dimensional graphene (3D-G) to prepare CoPc/3D-G catalysts used for oxygen reduction reaction (ORR). 3D-G is made from coal tar pitch with nano MgO as template and KOH as activation agent. Raman spectra indicate that 3D-G is multi-layered. Transmission electron microscopy images show that CoPc/3D-G retains the mesoporous foam structure of 3D-G and CoPc is dispersed homogeneously on the surface of 3D-G. CoPc/3D-G shows a half-wave potential of 0.85 V vs. RHE in oxygen-saturated solution of 0.1 M KOH, which is 50 mV higher than that of 6 wt% Pt/C. The electron transfer number of CoPc/3D-G is 3.99 at 0.65 V vs. RHE, indicating that oxygen reduction is catalyzed mainly via a four-electron process. CoPc/3D-G exhibits a current density loss of 10% after 40, 000 s in chronoamperometry tests, while CoPc/C lost 17.5% after the same period.